Kinematics and performance analysis of a serial hip assistive mechanism. (April 2018) - Li, Jianfeng; Shen, Bowen; Zhang, Leiyu; Tao, Chunjing; Ji, Run
A serial assistive mechanism was proposed for the hip adduction/abduction and flexion/extension motion assistance, which is kinematically compatible with human hip complex. As the mechanism is connected to the wearer, a 2-degree-of-freedom human–robot closed chain is formed. The closed-form position solution of the assistive mechanism was investigated, the Jacobian matrixes which map the velocity and force from the active joint space of the assistive mechanism to hip joint space were derived, and five new indices for performance evaluation of the assistive mechanism were defined. On the basis of the presented position solution and evaluation indices, the performances of the assistive mechanism during a human gait cycle, such as the human–robot motion offset, the motion and force assistive characteristics, were analyzed through the examples with seven wearing error models. The results show that the assistive mechanism has several distinct advantages including small human–robot motion offset, favorable motion assistive isotropy, and high force assistive efficiency. The proposed indices can evaluate the assistive feature adequately, and the serial assistive mechanism is applicable to the 2-degree-of-freedom hip adduction/abduction and flexion/extension motion assistance.